Model Pembelajaran Berbeda pada Keterampilan Proses Sains Siswa dalam Pembelajaran Biologi Sumbawa, Indonesia - Supratman Supratman; Eryuni Ramdhayani (Peneliti.net, 2022)
Science process skills as one of the 21st century skills are important to be empowered. Empowerment of science process skills can be done by applying innovative learning models, namely POPBLSTAD, POBL and STAD. The purpose of this study was to determine the effect of different learning models on students' science process skills in learning biology. The design of this study used a quasi-experimental design with a Pretest Posttest Nonequivalent Control Group Design to examine the effect of the POPBLSTAD, POPBL, and STAD models on science process skills. Determining the sample in this study using the Random Sampling technique in classes that have gone through trials. The research instrument used a multiple choice test with indicators of science process skills, namely identifying variables, estimating data, formulating hypotheses, operationally defining, and conducting experiments. Data analysis in this study used statistical inferential analysis of covariance (ANACOVA) one way with a significance level of 5%. The results of this study indicate that there is an influence of the learning model on students' science process skills. The results of the BNT test show that the POPBLSTAD learning model has significant skills compared to the other three models.